Tubular dysfunction and microalbuminuria in insulin dependent diabetes. Issue 3 (March 1988) - Walton, C; Bodansky, H J; Wales, J K; Forbes, M A; Cooper, E H
Abstract : The nature of microproteinuria in the early years of insulin-dependent diabetes was investigated in a cross sectional study of 80 children with insulin-dependent diabetes and 40 normal children. Urinary excretion of three low molecular weight proteins: alpha-1-microglobulin, beta-2-microglobulin and kappa light chains was used as an index of proximal renal tubular function. The first urine samples of the morning were collected and excretion of proteins measured was expressed as ratio of protein to creatinine. There was a strong correlation between excretion of alpha-1-microglobulin and chi light chains and their excretion was significantly higher in diabetic children indicating decreased proximal tubular reabsorbtion. The excretion of beta-2-microglobulin was found to be an unsatisfactory index of proximal tubular function. Urinary albumin excretion was not significantly raised in diabetic children and did not correlate with urinary alpha-1-microglobulin or chi light chain excretion. Glycaemic control might influence proximal tubular function as both urinary glucose concentration and glycosylated haemoglobin showed correlations with urinary alpha-1-microglobulin excretion and with urinary chi light chain excretion.